The Impact of Sports Infrastructure and Pedagogical Competence of Physical Education Teachers on the Increase of Volleyball - Tuan Anggi Nuhudawi S; Sunarno, Agung; Suprayitno; Oktariska, Salsa (JUARA : Jurnal Olahraga, 2024)
This quantitative study investigates the impact of sports infrastructure and the pedagogical competence of physical education (PE) teachers on the interest in volleyball among junior high school students in Medan City, Indonesia. With a focus on addressing the sedentary lifestyle prevalent among adolescents, the research aims to contribute to the enhancement of sports education by examining these key factors. Employing a structured questionnaire and utilizing SPSS version 27 for data analysis, the study analyzed responses from 54 participants through t-test, F-test, and coefficient of determination (R-square) tests. Findings indicate that both the quality of sports infrastructure and the competence of PE teachers significantly influence students' sports interest. Specifically, well-maintained facilities and skilled educators were found to collectively account for 67.1% of the variance in sports interest, highlighting their pivotal roles in promoting physical activities. The study underscores the need for a holistic approach in sports education, emphasizing the development of sports facilities and the enhancement of teacher training to foster a more inclusive and engaging sports culture among students.